2018
DOI: 10.1111/jocn.14604
|View full text |Cite
|
Sign up to set email alerts
|

CALD Assist—Nursing: Improving communication in the absence of interpreters

Abstract: The proposed app can be used to reduce variances in practice and provide a timely and positive patient experience for patients from NESBs who are unable to communicate in English during hospital admissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 17 publications
(26 reference statements)
1
19
0
Order By: Relevance
“…Google Translate, a web-based tool, is available but low translation accuracy of medical terminologies has the potential for distress and harm [ 78 ]. Current applications such as CALD- Assist (an Australian application) that uses pre-recorded text words and phrases along with pictures and videos for allied health and nursing staff to facilitate communication when interpreters are not available or not practical [ 79 ] notwithstanding the applications have shown improved satisfaction for communication between consumers and health professionals. More research is needed to understand the patient safety implications of them.…”
Section: Discussionmentioning
confidence: 99%
“…Google Translate, a web-based tool, is available but low translation accuracy of medical terminologies has the potential for distress and harm [ 78 ]. Current applications such as CALD- Assist (an Australian application) that uses pre-recorded text words and phrases along with pictures and videos for allied health and nursing staff to facilitate communication when interpreters are not available or not practical [ 79 ] notwithstanding the applications have shown improved satisfaction for communication between consumers and health professionals. More research is needed to understand the patient safety implications of them.…”
Section: Discussionmentioning
confidence: 99%
“…By using DCAT before the consultation in a waiting room, the actual appointment is not disturbed or prolonged. This also distinguishes our approach from those which introduce a digital ad-hoc translation (e.g., using Google translate during the consultation) [28][29][30] and apps that only allow health care providers to communicate preselected phrases and are therefore not self-administered by patients [14,15,17,18]. Furthermore, the DCAT app is free to download, making it accessible to all clinics that have a digital device they can circulate.…”
Section: Discussionmentioning
confidence: 99%
“…This can foster miscommunication between the physician and patient and contribute to an incomplete list of symptoms, ultimately leading to poor quality of care [12]. Although there are several tools to address this problem, including multilingual symptom reporting questionnaires, limited efforts have been made to develop digital tools for multilingual or intercultural settings [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…25 In addition, tools that facilitate basic communication between CALD patients and clinicians in the absence of interpreters are needed to assist patient engagement and increase clinicians' confidence in their interactions with patients speaking other languages. 28,29 The way distress and emotional issues are conceptualised and reported may differ between cultures. 30,31 A review of DT and PC translations worldwide identified that different language versions generally show good psychometric properties and are conceptually equivalent to the English-language version.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, an analysis of conversations between clinicians and immigrant patients showed that 20% of informational or emotional cues were not translated by interpreters and therefore clinicians may not have had an opportunity to discuss patients' concerns 25 . In addition, tools that facilitate basic communication between CALD patients and clinicians in the absence of interpreters are needed to assist patient engagement and increase clinicians' confidence in their interactions with patients speaking other languages 28,29 …”
Section: Discussionmentioning
confidence: 99%